Randomized Factorial Trial of Phone-Delivered Support Counseling and Daily Text Message Reminders for HIV Treatment Adherence. - Kalichman, Seth C; Kalichman, Moira O; Cherry, Chauncey; Eaton, Lisa A; Cruess, Dean; Schinazi, Raymond F (Journal of acquired immune deficiency syndromes (1999), 2016)
HIV infection is clinically managed with antiretroviral therapy (ART), but only with sustained adherence. Cost-efficient interventions to improve and sustain ART adherence remain a pressing priority for populations challenged by non-adherence.